GAMBARAN TINGKAT KECEMASAN PADA WARGA BINAAN PEREMPUAN DI LEMBAGA PERMASYARAKATAN PEREMPUAN KELAS IIA DENPASAR - Adiari, G.A.A; Yudhawati, NLP.S; Sri Muryani, N.M (Bali Health Published Journal, 2021)
Background: Anxiety in female residents is a concern experienced by the target citizens during their prison term.The impact of prolonged anxiety leads to mental disorders. Anxiety in female assisted citizens can be experienced by all the target citizens who are in prison, research conducted earlier in 2020 obtained 55.9% of female target citizens experience mild anxiety. This study aims to find out the Picture of Anxiety Level in Women's Assisted Citizens in The Women's Society Class IIA Denpasar. Method: Type of quantitative research with Cross Sectional approach. sampling with purposive sampling techniques with 115 respondents. Results : Research conducted to 115 inmates at the Class IIA Denpasar Women's Society About anxiety levels classified as mild anxiety as many as 51 respondents (44.3%), based on adult age (26-45) as many as 75 respondents (65,65.3%), based on adult age (26-45) as many as 75 respondents (65,65 2%), based on the case of most narcotics as many as 97 respondents (84.3%), based on the length of time in prison that is 1-4 years as many as 53 respondents (46.1%), based on the last education of most high schools as many as 62 respondents (53, 9%) and marital status were mostly unmarried as many as 43 respondents (37.45%). Conclusion: The level of anxiety of women-assisted citizens in the Class IIA Denpasar Women's Society is mild